COMMUNICATIVE LANGUAGE TESTING: KEY CONCEPTS AND PRINCIPLES (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
Communicative Language Testing (CLT) represents a paradigm shift in language assessment, focusing on learners’ ability to use the target language effectively in real-life contexts. Unlike traditional tests that prioritize grammar and vocabulary knowledge, CLT evaluates communicative competence, integrating linguistic, sociolinguistic, and pragmatic components. This approach aligns with modern pedagogical methods, emphasizing interaction, meaningful communication, and contextualized tasks.